How Does the R&D Cooperation Path of Supply and Demand Network Enterprises Evolve? - Jianjia He (IEEE, 2021)
To explore the complexity and uncertainty of R&D cooperation in supply and demand network (SDN) enterprises, this study used the evolutionary game theory and the duplicate dynamic equation to construct the R&D cooperation strategy selection model. Based on the perspective of knowledge spillover, the model investigated the influence of knowledge spillover, government reward, government penalty, cooperative cost, and R&D cooperation risk in the cooperation of SDN enterprises. Next, this study analyzed the stability and the system evolution path of the model. Finally, it used numerical simulation to vary the rationality of the model. Based on this research, there are some conclusions can be obtained: Firstly, the evolution of R&D cooperation strategy for SDN enterprises may eventually stabilize at cooperation or selfishness strategy under different situations. As for which strategy is ultimately stable, it is closely related to the construction of the initial payment matrix and the selection of initial parameters. Secondly, there are two stable states in the game system: cooperation and selfishness. If one party chooses cooperation and the other party chooses selfishness, the system will not be stable. Thirdly, knowledge spillover degree, government reward, government penalty, government penalty, cooperation cost, and cooperation risk are important factors that can influence the cooperation evolution of SDN enerprises. Fourth, under certain situations, if knowledge spillover degree, government reward, and government penalty increase, cooperation cost and cooperation risk decrease, the R&D cooperation in SDN enterprises will be improved. Related implications and suggestions are finally proposed, which can offer some valuable guidance for the development of SDN enterprises.